Metastatic basal cell carcinoma to the bone: a case of bone metastatis in unfrequent sites - Olga Nigro; Claudio Chini; Ilaria Gioia Angiola Marcon; Annamaria De Giorgi; Linda Bascialla; Elisa Gallerani; Alice Giaquinto; Diego De Palma; Maurizio Lombardo (PAGEPress Publications, 2022)
Basal cell carcinoma (BCC) is the most common malignant tumor of the skin. Despite the indolent nature, metastatic BCC can occur, albeit rarely. Metastasis to the bone are very rare. From its approval, mBCC patients are treated with vismodegib, a selective hedgehog pathway inhibitor. Unfortunately, in recent period, it was demonstrated an emergence of drug resistance, due to Smoothened (SMO) mutation. To date, several groups are studying the effectiveness of immunotherapy in BCC. Clinical trials with Immune Checkpoint Inhibitors are ongoing. We report the rare case of a man with multiple bony metastasis, with a resistance to vismodegib, and we evaluated all manuscripts in literature reporting bone metastasis. Moreover, we review all the manuscripts in literature reporting bone metastasis, and we summarize the main therapeutic strategies, and the further perspectives.